Storm wave modeling with swan comparison of measurement data and modeling results for the storm MUIFA 11/2004 - Hung, Nguyen Manh; Thuy, Do Le; Dien, Duong Cong (Vietnam Journal of Mechanics, 2005)
With the average of 4-5 storms hitting the Vietnamese coastline every year, our country is suffering from great damage of infrastructures and lost of human life. Most storms induce significant waves which, especially in the coastal zones, can destroy houses, coastal structures and move large amounts of sand from beaches to offshore resulting in shoreline erosion. Therefore modeling of storm waves is an important task of engineers, scientists, weather forecasting specialists of our country. In order to meet the need of mitigation storm effects, to improve the storm wave forecasting capability in general and to study the coastal evolution in the Red River Delta (RRD) in particular, the authors have developed the Sı\TAN model for the storm wave calculation in the East Sea. In the paper some formulations of the model has been used to get the best agreement with the measured wave field in the storm MUIFA 11 /2004. The wind and wave data at the oil platform MSPl and wave height field over the sea were used to compare the model results. The obtained results afford the promising of using the SWAN model in research and weather forecast.